On the 95th anniversary of the Honored Professor of Lomonosov Moscow State University Yuri Mikhailovich Romanovsky - Priezzhev, Alexander Vasil'evich; Tuchin, Valery Viсtorovich (Известия Саратовского университета. Новая серия Серия: Физика)
-